A pooled analysis of pacemaker implantation after Perceval sutureless aortic valve replacement. (17th May 2021) - Moscarelli, Marco; Santarpino, Giuseppe; Athanasiou, Thanos; Mastroroberto, Pasquale; Fattouch, Khalil; Nasso, Giuseppe; Speziale, Giuseppe
Abstract: OBJECTIVES: We performed a literature meta-analysis to estimate the rate of pacemaker implantation after Perceval sutureless aortic valve replacement. METHODS: Pertinent articles were identified from the PubMed, Google Scholar, Ovid MEDLINE and Ovid EMBASE databases. Eligible studies reported the de novo incidence of postoperative pacemaker implantation after Perceval valve surgery. Among 394 articles retrieved, 26 studies including 9492 patients met the inclusion criteria. RESULTS: The pooled event rate for postoperative pacemaker implantation was 7% [95% confidence interval (CI) 6–9%]; however, significant heterogeneity was observed across studies. In a sub-analysis, there was no difference between the rates of pacemaker implantation calculated from multicentre and registry studies (8 studies, 6845 patients; 7%, 95% CI 5–10%) and single-centre studies (18 studies, 2647 patients; 7%, 95% CI 5–9%; P  = 0.75). Implantation rates were similar in high-volume studies (16 studies, 9121 patients; 7%, 95% CI 5–8%) than in low-volume studies (10 studies, 371 patients; pooled rate: 7%, 95% CI 4–14%; P  = 0.5). Postoperative pacemaker implantation rates tended to decrease over time. CONCLUSIONS: With a pooled event rate of 7%, postoperative pacemaker implantation remains an important limitation of Perceval sutureless valve surgery, although we observed a degree of variability across included studies. The resultant findings provide a useful estimate for physicians and patients and can serve as a benchmark for future comparative studies. PROSPERO registration number: CRD42020188397. Abstract : Aortic valve replacement (AVR) with the Perceval sutureless aortic valve (Livanova PLC, London, UK) is associated with excellent operative and clinical outcomes, yet concerns still exist regarding the postoperative incidence of new atrioventricular conduction disturbances requiring permanent pacemaker implantation (PPI) [1, 2].